Efisiensi Alokasi Aset untuk Meningkatkan Kinerja Keuangan Perusahaan pada Industri Manufaktur Indonesia - Sugiharto, Amo; Heriyanti; Yulhendri; Al Rifqi, Fiere Ahmad; Wibowo, Pahul Tri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Termination of Employment that has been ongoing, especially in the manufacturing industry, are contrary to the tendency of investor interest, especially foreign investors, to invest increasing capital in line with the growth and development of industry and the absorption of labor after the pandemic, is an interesting issue to study, paying attention to the level of efficiency of the assets used by the company to generate sales. Therefore, this research aims to pay attention to sales generated through the use of assets. Research was conducted on the manufacturing industry on the Indonesia Stock Exchange (IDX) which was listed for 3 (three) years from 2021 to 2023 using company financial data as a basis for data processing using financial ratio analysis. The research results show TATO (Total Asset Turnover) of the manufacturing industry is 0.94 times lower (less) than 1.1 times (0.94 < 1.1), so it can be concluded that TATO (Total Asset Turnover) of the manufacturing industry is not good.